Penerapan Restoratif Justice terhadap Tindak Pidana Adat dalam Undang-Undang No. 20 Tahun 2025 tentang Hukum Acara Pidana - Abdul Hayy Nasution; Nyak Amini (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the provisions governing restorative justice within Indigenous customary communities, where the living law recognized and practiced by such communities is regulated under Article 2 paragraphs (1) and (2) of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP). The provisions concerning restorative justice in criminal proceedings are further regulated under Articles 79–88 of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP). This study seeks to address the following research questions: (1) how are the provisions for the application of restorative justice to customary criminal offenses regulated under Law Number 20 of 2025 concerning the Criminal Procedure Code, and (2) how is the implementation of restorative justice for customary criminal offenses carried out under the same law. This research employs a normative legal research method, which is appropriate because the study focuses on examining statutory regulations and legal principles. The objectives of this study are to analyze the legal provisions governing the application of restorative justice to customary criminal offenses under Law Number 20 of 2025 concerning the Criminal Procedure Code and to examine its implementation within the Indonesian criminal justice system.